Pengembangan Bahan Ajar Panca Indera Berbasis Multiple Intelligences Pada Siswa Kelas I Sekolah Dasar - Fauziah Azizah Amir (Institut Agama Islam Negeri Palopo, 2020)
The main purpose of this research is to develop the teaching materials of five senses based on multiple intelligences which are valid, and to know the level of effectiveness of the materials teaching the five senses, a multiple intelligences to the observation of students ' activities and the study results test. This research uses research methods Research & Development (R&D). To develop the product, researchers use ADDIE's model of development consisting of five phases: 1. Analysis, 2. Design, 3. Development, 4. Implementation, and 5. Evaluation. The teaching materials are developed in the form of a multiple intelligences-based five senses module which is the subject of a trial is 20 students. The technique of data collection in this study is the students ' intelligences test, validation sheet, observation sheets, student activities, and student study results tests. The data analysis technique used by researchers to test the valid is analyzed quantitatively and to test its effectiveness will be in quantitative analysis. For the analysis quantitatively used descriptive statistics